Nutrition and physical activity professional education in gastrointestinal oncology: a national multidisciplinary survey. Issue 3 (14th July 2020) - Hilmi, Marc; Pellat, Anna; Benoit, Olivier; Foucaut, Aude-Marie; Mino, Jean-Christophe; Kauffmann, Agnes; Rochet, Fanny; Heuze, Emmanuel; Pudlarz, Thomas; Naoun, Natacha; Garcia-Larnicol, Marie-Line; Delpeut, Christine; et al.
Abstract : Objectives: Sarcopenia, present in more than 50% of digestive oncology patients, has a negative impact on clinical outcomes. Nutrition and adapted physical activity are two major interventions for the management of sarcopenia. However, young hepato-gastroenterologists, oncologists and surgeons in France have limited awareness on these topics. We aimed to evaluate the need for training programmes of physicians (residents and senior doctors) involved in digestive oncology on nutrition and adapted physical activity. Methods: A 42-question survey was developed, by a working group of clinicians, dieticians and adapted physical activity teachers, to assess five areas related to demographics of respondents, nutrition practices, nutrition training, adapted physical activity practices and adapted physical activity training. The national survey was undertaken between April and July of 2019. Results: 230 physicians participated in the survey; 34% were hepato-gastroenterologists, 31% were oncologists, 23% were surgeons and 40% were residents. Sixty-one per cent of participants had received training in nutrition and only 21% in adapted physical activity. Ninety per cent of the physicians expressed their desire for more effective training on these two topics. Disparities in clinical practices were observed between hepato-gastroenterologists, oncologists and surgeons. Conclusions: More initial and continuing training on nutrition and adapted physical activity is needed for French physicians in the current digestive oncology clinical practice.